2019
DOI: 10.1186/s12888-019-2382-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting recurrence of depression using lifelog data: an explanatory feasibility study with a panel VAR approach

Abstract: BackgroundAlthough depression has a high rate of recurrence, no prior studies have established a method that could identify the warning signs of its recurrence.MethodsWe collected digital data consisting of individual activity records such as location or mobility information (lifelog data) from 89 patients who were on maintenance therapy for depression for a year, using a smartphone application and a wearable device. We assessed depression and its recurrence using both the Kessler Psychological Distress Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Four of these studies reported on prodromes of relapse or recurrence in patients whose MDD was judged to be in remission [16, 25, 27, 28]. In 1 study [16], during a 6-month period following discontinuation of antidepressant drugs, 4 out of 15 patients with a first MDE relapsed and required further treatment with antidepressants.…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies reported on prodromes of relapse or recurrence in patients whose MDD was judged to be in remission [16, 25, 27, 28]. In 1 study [16], during a 6-month period following discontinuation of antidepressant drugs, 4 out of 15 patients with a first MDE relapsed and required further treatment with antidepressants.…”
Section: Resultsmentioning
confidence: 99%
“…More research is needed here that also picks up recent findings regarding the interplay between these factors. For example, Kumagai et al ( 72 ) showed that long sleep time was an important risk factor for the recurrence of depression. However, with the current data, it was not possible singling out specific sleeping times.…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that the rate of depression in this population might simply demonstrate a brief, transient stage during this period of instability. However, even after treatment, the risk of relapse for depression is high, with research suggesting a 10-80% rate of recurrent episodes (dependent on depression severity) ( Holma et al, 2008 ; Kessler and Bromet, 2013 ; Kumagai et al, 2019 ; Köhler et al, 2015 ; Limosin et al, 2004 ). Therefore, identifying the risk factors for depression within this population may not only alleviate suffering during equivalent periods of precariousness, but further improve the chance of mental stability in later life.…”
Section: Discussionmentioning
confidence: 99%